2007
DOI: 10.1590/s1516-635x2007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and mannanoligosaccharides in broiler diets

Abstract: campus, and aimed at evaluating the effect of the inclusion of flavonoids along with mannan oligosaccharides (MOS) as compared to other additives on the performance, carcass and parts yields, and meat quality of broilers reared from 1 to 42 days of age. A total number of 1500 Cobb broilers were distributed according to a completely randomized experimental design into five treatments, with six replicates of 50 birds each. Treatments consisted of a control group, probiotic 1, probiotic 2, antibiotic, and flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…In agreement with our results, in a comparative study, Cömert (2004) reported that the BW and gain were not affected by the dietary MOS and probiotic addition in bronze turkeys which advanced in .2 MOS -mannan oligosaccharide; P -probability; SEM -standard error of the means (Pooled); NS -non-significant; HDL -high density lipoprotein; LDL -low density lipoprotein weeks (from 7 to 21 weeks). Similarly, Batista et al (2007) reported that the BW and gain were not affected by both prebiotic and probiotic supplementation in broilers. In contrast to other investigations with MOS, improvements in the BW or gain have been reported (Stanley et al, 2000;Sims et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results, in a comparative study, Cömert (2004) reported that the BW and gain were not affected by the dietary MOS and probiotic addition in bronze turkeys which advanced in .2 MOS -mannan oligosaccharide; P -probability; SEM -standard error of the means (Pooled); NS -non-significant; HDL -high density lipoprotein; LDL -low density lipoprotein weeks (from 7 to 21 weeks). Similarly, Batista et al (2007) reported that the BW and gain were not affected by both prebiotic and probiotic supplementation in broilers. In contrast to other investigations with MOS, improvements in the BW or gain have been reported (Stanley et al, 2000;Sims et al, 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, probiotics (Patterson and Burkholder, 2003) and MOS have the potential to enhance growth rate, feed efficiency, and livability in poultry species (Shane, 1999;Patterson and Burkholder, 2003). On the other hand, some of the reports failed to observe a positive effect of feeding with yeast on growth performance in turkeys (Bradley and Savage, 1995) and broilers (Batista et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…No differences in broilers' DWG, feed intake, final body weight and carcass characteristics were found after flavonoid and mannanoligosaccharide (300 ppm) dietary incorporation (Batista et al . 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In the paper by Kraemer investigations are listed which show no increase in intake of broilers after addition of flavonoid phytogenics. 30,31 Blank and Wolffram observed an increased feed intake and improved growth rates in weaning pigs fed elder pomace as a known source of polyphenols. 32 This effect was seen as a consequence of an increased palatability of feed.…”
Section: Feed Intakementioning
confidence: 98%
“…However, the simple addition of plant‐derived colorants will not always foster intake. In the paper by Kraemer investigations are listed which show no increase in intake of broilers after addition of flavonoid phytogenics . Blank and Wolffram observed an increased feed intake and improved growth rates in weaning pigs fed elder pomace as a known source of polyphenols .…”
Section: Effects Of Use In Animal Nutritionmentioning
confidence: 99%